Reconfigurando la canción, reinventando la nación: La folclorización de la música popular en brasil y en chile en los años cuarenta y cincuenta - Garcia, Tânia da Costa [UNESP] (My University, 2012)
At the middle of the twentieth century, between the forties and the fi fties, especially after the Second World War, the endless debate concerning national identity was taken up again in Latin America with a new focus. Mass culture, especially popular music with ties to the music industry, was shaped by its great capacity to spreadshown through its assorted forms of production, circulation and consumption- as one of the main areas of dispute related to the question of what is considered to be national. During that period there were important debates in Brazil and Chile about the selection, preservation and perpetuation of a certain repertoire of popular urban music as being representative of national folk music. These debates, which are analyzed starting from discursive representations driven by the written press, in both the specialized academic and the large-circulation press, constitute the central focus of this article.
Keywords: Folk music; Modernity; National identity; popular music; Tradition